Willingness to pay for improved solid waste management and associated factors among households in Debre Berhan town, North Shoa Zone, Amhara, Ethiopia, 2022 - Chernet, Dawit; Sema, Wondimu; Gebeyehu, Amare; Wogayehu, Belachew Tekleyohannes (Frontiers in Sustainability, 2024)
Abstract Background: The willingness to pay for better solid waste management is a system designed for households to contribute a maximum amount of money to service improvement. Objectives: This study determined the willingness to pay for improved solid waste management and associated factors among households in Debre Berhan Town, Ethiopia, 2022. Methods: A community-based cross-sectional study design was used in Debre Berhan Town, from June to July 2022. Multistage sampling techniques were used to select household heads using semi structured and pre-tested questionnaires. The data was entered using Epi-data version 4.6 and analyzed using Stata version 14. The univariable Tobit regression model was used for the multivariable Tobit regression model. The relationship between dependent and independent variables was declared statistically significant in the final model at a p-value of ≤ 0.05 in the 95% confidence interval. Result: This study included 518 households, with a response rate of 99.23%. Four hundred seventy-two households 91.1% (95% CI: 88.1-93.5) reported a willingness to pay for improved solid waste management. The average monthly willingness to pay was 54.83 Ethiopian Birr. Amount of solid waste generated (β:10.49; 95% CI: 2.85–18.12), knowledge (β:7.33; 95% CI: 2.43–12.22), perception (β: 10.01; (95% CI: 5.83–14.19), monthly income (β: 13.23; 95% CI: 6.20–20.26), education level (β: 14.30; 95% CI: 3.48–13.63), house ownership (β: 8.56; 95% CI: 3.48–13.63), family size (β:3.88; 95% CI:2.01-5.74), and female household heads (β:5.73; 95% CI: 1.73–9.70) were significantly associated factors. Conclusion: Willingness to pay for improved solid waste management services was high. The town municipality should install an improved solid waste management system by using this initiation of households' participation in willingness to pay contributions for solid waste management services to solve budget constraints. Keywords: Contingent Valuation Method, Debre Berhan Town, Solid waste, Willingness to pay, Ethiopia.